Impact of Innovation and Entrepreneurship Education in a University Under Personality Psychology Education Concept on Talent Training and Cultural Diversity of New Entrepreneurs - Li, Mengru; Wang, Tingting; Wu, Yanhui (Frontiers in Psychology, 2021)
The purpose of this study is to explore the cultivation of university students’ innovation and entrepreneurship as well as its influence on talent training and culture diversity. First of all, based on the combination of theoretical analysis and practical investigation, the entrepreneurship of college students and the basic situation of cultural diversity cultivation were discussed. The research objects involve students of different genders, grades, majors, and family backgrounds. Second, the reliability and validity of the scale were tested, and the survey data were analyzed after eliminating the invalid items. It is found that the average score of college students’ entrepreneurship is 3.428, and the score of innovation spirit dimension is 3.61, the highest in the dimensions; the score of forward-looking dimensions is 3.25, which is the lowest; the variance of leadership dimension is the lowest. The variance of the forward-looking dimension is the greatest. According to the analysis of different types of students’ scores, freshmen score lower in innovation dimension and challenge dimension, female students’ challenge spirit is slightly higher than that of males, and the leadership dimension score of science students is higher. Based on the survey results of cultural diversity training in colleges and universities, the average score is 3.343, the scores of course teaching and educational achievement are lower, and the score of cultural activity dimension is the highest. Liberal arts students have higher scores in cultural diversity, and the senior students have low scores in cultural diversity cultivation due to the limited time. This study has been considered in a comprehensive manner. It provides a scientific theoretical basis for carrying out innovation and entrepreneurship education as well as cultural or nutritional activities in colleges and universities, and thus has a significant practical value.